2017
DOI: 10.1123/ijspp.2016-0396
|View full text |Cite
|
Sign up to set email alerts
|

Within-Season Distribution of External Training and Racing Workload in Professional Male Road Cyclists

Abstract: Purpose:To describe the within-season external workloads of professional male road cyclists for optimal training prescription. Methods: Training and racing of 4 international competitive professional male cyclists (age 24 ± 2 y, body mass 77.6 ± 1.5 kg) were monitored for 12 mo before the world team-time-trial championships. Three within-season phases leading up to the team-time-trial world championships on September 20, 2015, were defined as phase 1 (Oct-Jan), phase 2 (Feb-May), and phase 3 (June-Sept). Dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 13 publications
(12 reference statements)
2
24
1
Order By: Relevance
“…Although the performance levels of subjects are well defined, data pertaining to maximal aerobic capacity, or volume and intensity of training were not available. As such, characterization of training within this group was based on previous reports using athletes of a similar performance level 44 . Radial ɛ was not reported in this study, due to poor reproducibility of this parameter (CoV 19%, ICC 0.714) 33 .…”
Section: Discussionmentioning
confidence: 90%
“…Although the performance levels of subjects are well defined, data pertaining to maximal aerobic capacity, or volume and intensity of training were not available. As such, characterization of training within this group was based on previous reports using athletes of a similar performance level 44 . Radial ɛ was not reported in this study, due to poor reproducibility of this parameter (CoV 19%, ICC 0.714) 33 .…”
Section: Discussionmentioning
confidence: 90%
“…It should be noted that this study was carried out during a period when cyclists are reducing their training and competitions (late September-mid December) which involves training misadaptations (physiological and metabolic changes) [45,46]. These changes may justify the drop in the performance at sub-maximal and maximum intensities for placebo in our study.…”
Section: Incremental Testmentioning
confidence: 97%
“…One such study focused on a runner who participated in 75 races over three years (38 road races of marathon distance or less, 18 ultramara-thon races and 19 trail running races) and who performed mostly low-intensity training (Takayama et al, 2018). Another study investigating the year-long training distribution for four professional cyclists showed that the cyclists reduced the intensity and volume of their training in the weeks with no race to try to recover (Metcalfe et al, 2017). In Phase 2 of the present study, the subject runner performed mostly low-intensity training except for the races (Figure 3), and his TL in the weeks with no race tended to be low ( Figure 2).…”
Section: Discussionmentioning
confidence: 47%
“…It has also been found that an increase in creatine kinase activity is related to medium-intensity and high-intensity training (Petibois et al, 2002). Indeed, several studies have suggested the importance of low-intensity training for endurance athletes who participate in consecutive races within a short period of time (Metcalfe et al, 2017;Mujika, 2014;Takayama et al, 2018). One such study focused on a runner who participated in 75 races over three years (38 road races of marathon distance or less, 18 ultramara-thon races and 19 trail running races) and who performed mostly low-intensity training (Takayama et al, 2018).…”
Section: Discussionmentioning
confidence: 99%